Risk factors of hypotension during cesarean section with spinal anesthesia in parturients with COVID-19: a retrospective study in comparison with pregnant women without COVID-19 - Si Ra Bang; Gunn Hee Kim; Sung Jun Cho; Mi Jung Yoon (Anesthesia and Pain Medicine)
Background The incidence of hypotension in parturients with coronavirus disease (COVID-19) undergoing regional anesthesia remains controversial. This study aimed to investigate the incidence of hypotension during spinal anesthesia in parturients infected with COVID-19, as well as to identify associated risk factors. Methods This retrospective study compared COVID-19-positive parturients who underwent cesarean section under spinal anesthesia (COVID-19 group) with a control group between January 2017 and June 2022. We reviewed the medical records and collected the following information: basic patient characteristics, spinal anesthesia, and newborn-related data. Results Compared with the control group, the COVID-19 group did not show any significant differences in terms of hypotension occurrence and vasopressor usage. A positive correlation was noted in the COVID-19 group between heart rate and duration of hospital stay (P < 0.001, Spearman’s rho = 0.422). In subgroup analysis of the COVID-19 group, group with a baseline heart rate ≥ 100 (group H) had lower Apgar scores at 1 min, longer hospital stays, and more severe COVID-19 symptoms than the with a baseline heart rate < 100 (group L). Moreover, in group H, there was a positive correlation between the heart rate and the lowest systolic blood pressure after spinal anesthesia (P = 0.012, Spearman’s rho = 0.528). Conclusions Parturients with COVID-19 do not appear to have a higher risk of hypotension during cesarean section under spinal anesthesia than those without COVID-19. Given the close association between preoperative heart rate and extent of hypotension in parturients with COVID-19 undergoing spinal anesthesia, vigilant monitoring of vital signs by anesthesiologists is crucial during the perioperative period.